Total Flavonoid Content and In Vitro Anti-Inflammatory Potentials of Kombucha with Enrichment of Butterfly Pea (Clitoria ternatea) Flower Extract - Wahyanto, Kharisma Nareswari; Agustini, Rudiana (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Kombucha is a fermented beverage from tea (Camellia sinensis) that is claimed to be beneficial for several medical ailments. Several studies have conducted nutritional enrichment of kombucha to optimize its nutritional benefits. One of the native Indonesian plants that can be utilized as nutritional enrichment material is the butterfly pea (Clitoria ternatea) flower. Its nutrition is expected to increase the health benefits of kombucha Camellia sinensis. Kombucha has beneficial compounds such as flavonoids that have potential applications in medical chemistry due to its anti-inflammatory properties. This study aims to enrich the valuable nutrition and test the in vitro anti-inflammatory potentials of kombucha, conducted by formulating kombuchaCamellia sinensis with Clitoria ternatea flower extract addition (0; 0.5; 1; 1.5; 2)% (m/v), the chemical characterization including pH value test using digital pH meter and total flavonoid content (TFC) using colorimetric (AlCl3) assay) with quercetin as its standard, and in vitro anti-inflammatory activity test using the red blood cell (RBC) membrane stabilization method. The result showed that the pH value of kombucha had met the consumption quality standard (3-4), starting from 3,30 + 0,00 (0%) to 3,66 + 0,01 (2%). The flavonoid content increased from 38,89 + 0,05 mgQE/g (0%) to 126,73 + 0,13 mgQE/g (2%). Kombucha samples showed anti-inflammatory activity potentials with the best IC50 value of 140,22 ppm (2% addition). The data from this study were analyzed using a one-way ANOVA statistical test. It shows there is an influence from the addition of Clitoria ternatea to the TFC result (p<0,05), and it continued to Duncan's Multiple Range test (DMRT) that showed sample F0 to F4 were significantly different from each other (p<0,05). In conclusion, the enrichment of kombucha (Camellia sinensis) using Clitoria ternatea flower extract has been proven to increase the health-beneficial compound (flavonoids) and have potential anti-inflammatory activity.